Analisis kinerja kegiatan rehabilitasi hutan dan lahan berdasarkan value for money - Novia Nurdia Ningsih; Siti Masyithoh; Ibnu Abni Lahaya (Faculty of Economics and Business Mulawarman University, 2017)
Dinas Kehutanan Provinsi Kalimantan Timur city of Samarinda as public sector organizations in terms of the achievement of performance declines especially Performance prosentasenya Forest and land Rehabilitation Program. The research aims to know the performance of forest and land Rehabilitation Programs based on Value For Money in the Forestry town of Samarinda, East Kalimantan province. This research is a descriptive qualitative research with the object examined was the Realization of financial data of Forestry of East Kalimantan province city of Samarinda on government agency performance accountability Reports (LAKIP) Forestry Samarinda city of East Kalimantan province period in 2014. The data collection method used is the documentation and field research. Based on the results of the analysis are obtained, namely the economic value of the Forest Program activity Rehabilitation and land conducted Forestry province of East Kalimantan can be measured by comparing the primary inputs (funds realized) and t he secondary form of input (human resources / Procurement Advice Team and infrastructure). Calculation analysis of the results of performance assessment working paper Department of Forestry of East Kalimantan province obtain economic value of 89%. The economic performance of the value 85% up to 100% is the value entered on the performance categories are quite economical. Based on the results of the measurement of the efficiency of data analysis on Forest Rehabilitation activity programme and noted that for the period 2014 program activities can be efficiently. In the period 2014 Forestry Samarinda city of East Kalimantan province in carrying out the programme of activities can generate maximum output reaches 100% of the input with the use of only 89%. From the results of the calculation of the working paper analyses the performance assessment Value For Money Forestry Province of East Kalimantan obtained a value of 130% efficiency. The resulting effectiveness ratio of these activities during the year 2014 according to the working paper the assessment Value For Money that is 96,55%. By comparing the description value performance divided by the value of the performance output then the revenue percentage.